Improving Distress in Dialysis (iDiD): A tailored CBT self-management treatment for patients undergoing dialysis. - Hudson, Joanna L.; Moss‐Morris, Rona; Game, David; Carroll, Amy; Chilcot, Joseph (Journal of Renal Care, 2016)
Background There is significant psychological distress in adults with end-stage kidney disease (ESKD). However, psychological treatments tailored to address the unique challenges of kidney failure are absent. We identified psychological correlates of distress in ESKD to develop a cognitive-behavioural therapy (CBT) treatment protocol that integrates the mental health needs of patients alongside their illness self-management demands. Methods Studies which examined relationships between distress and psychological factors that apply in the context of ESKD including: health threats, cognitive illness representations and illness management behaviours were narratively reviewed. Review findings were translated into a CBT formulation model to inform the content of a renal-specific seven session CBT treatment protocol, which was commented on and refined by patient representatives. Results Health threats related to distress were grouped into four themes including: acute ESKD events, loss of role, uncertainty and illness self-management. Having pessimistic illness and treatment perceptions were associated with elevated distress. Non-adherence and avoidance behaviours were related to feelings of distress, whereas cognitive reappraisal, acceptance, social support and assertiveness were associated with less distress. Conclusions The dialysis-specific CBT formulation identifies the importance of targeting ESKD-specific correlates of distress to allow the delivery of integrated mental and physical health care. The ' Improving Distress in Dialysis (iDiD)' treatment protocol now requires further evaluation in terms of content, feasibility and potential efficacy.